PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 63 PEKANBARU - Wati, Wati; Marhadi, Hendri; Alim, Jesi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this research is to improve student learning outcomes IPA Class III SD Negeri 63 Pekanbaru with the implementation of Cooperative Learning Student Team Achievement Division (STAD ) mode. Based on the results of research and discussion can be seen that the implementation of cooperative learning Student Team Achievement Division (STAD) mode can increase the activity of third grade students of SDN 63 Pekanbaru in learning, this can be evidenced by increased activity of teachers at each meeting, where at the first meeting teacher activity only 58.33% with less category. Then increased at the second meeting of the first cycle as much as 16.67% to 75% with enough category. At the third meeting of the second cycle also increased as much as 12.50% to 87.50% with the good category and at the fourth meeting of the second cycle also increased as much as 8.33% to 95.83% with the exelence category. Student activity also increased at each meeting, where the first meeting of student activity only 54.17% with less category. Furthermore, at the second meeting of the first cycle be happened an increase of 16.66% to 70.83% with the category enough. Then in the third meeting of the second cycle increased by 12.50% to 83.33% with the good category and at the fourth meeting of the second cycle as much as increased 8.34% to 91.67% with the exelence category . The implementation of cooperative learning Student Team Achievement Division (STAD) mode can also improve learning outcomes Elementary School third grade students 63 Pekanbaru, where on the base score average value obtained by the students only 74.62, then in the first cycle increased to 80 , 77 an increase of 8.24%. In the second cycle, the average value of student learning outcomes increased to 89.42 an increase of 19.83%. Additionally, completeness individual student learning outcomes also increased, where the base score of individual students who completed only 14 people, in the first cycle an increase of 5 to 19 people. Then in the second cycle an increase of 5 to 24 people. Improved student learning completeness individually followed by an increase in the percentage of students in the classical mastery learning, where the base score of students who completed only 53.85%, the first cycle replicates an increase of 19.23% to 73.08, and the repetition cycle the percentage of students in classical mastery learning an increase of 19.23% to 92.31%.Keywords: STAD cooperative learning, learning outcomes